2001
DOI: 10.5860/crl.62.5.407
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Nature of Work in Academic Libraries

Abstract: A content analysis of 220 job advertisements that appeared in College & Research Libraries between 1973 and 1998 demonstrates that by 1998, all academic library jobs routinely included computer technologies, that instruction had become an integral part of reference work, and that behavioral skills, especially oral and written communication skills, had emerged as new job requirements. The master’s degree from a program accredited by the ALA continues to be widely accepted as the appropriate professional deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 7 publications
5
82
0
2
Order By: Relevance
“…5 At least one study has suggested that the ability to demonstrate one's teaching skills can improve one's chances of obtaining a position in a competitive professional market, and others have shown that there is a strong interest among many libraries in the formal evaluation of instruction provided by librarians. 6 Even work outside the classroom-for example, service on the reference desk, participation in scholarly communications initiatives-has increasingly been cast within the context of the librarian's role as teacher.…”
Section: Sco Walter Is Associate University Librarian For Services Anmentioning
confidence: 99%
“…5 At least one study has suggested that the ability to demonstrate one's teaching skills can improve one's chances of obtaining a position in a competitive professional market, and others have shown that there is a strong interest among many libraries in the formal evaluation of instruction provided by librarians. 6 Even work outside the classroom-for example, service on the reference desk, participation in scholarly communications initiatives-has increasingly been cast within the context of the librarian's role as teacher.…”
Section: Sco Walter Is Associate University Librarian For Services Anmentioning
confidence: 99%
“…As Cronin comments, "the introverted, bookish loner is clearly the antithesis of the type of individual sought by employers" [45]. Analysis of library job advertisements by Lynch and Smith in America [15] and Kennan et al in Australia [14] found that conventional librarianship skills over the years have become less important for employers, whereas personal skills such as creativity, flexibility, and communication have become increasingly important; these were seen as necessary to deal with the impact of rapid change within the profession. Goulding et al also comment that "[library] employers place a high premium on personal attributes such as enthusiasm, initiative, flair, interpersonal skills and commercial awareness" [13].…”
Section: Skills Qualities and Knowledge Of Academic Librariansmentioning
confidence: 99%
“…Today's academic librarians need a diverse set of skills, knowledge and competencies, many of which have not traditionally been associated with librarianship [12]. Library managers are increasingly valuing general and personal skills over traditional librarianship skills [3,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…37 Lynch and Smith noted that, "because the ALA-accredited degree is an accepted job requirement, the assumption of employers seems to be that a graduate's knowledge base will include knowledge of computer technologies as they relate to library and information science." 38 …”
Section: Technology Skillsmentioning
confidence: 99%